2010
DOI: 10.1155/2010/674575
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Natriuretic Peptides in Children before and after Treatment for an Atrial Septal Defect, a Patent Ductus Arteriosus, and a Coarctation of the Aorta—A Prospective Study

Abstract: Background and Objectives. We evaluated and compared the influence of treatment for atrial septal defect (ASD), patent ductus arteriosus (PDA), and coarctation of the aorta (CoA) on serum levels of N-terminal proatriopeptide and N-terminal probrain natriuretic peptide. Correlations between peptide levels and echocardiographic measurements were calculated. Patients and Methods. Peptide levels were measured and echocardiography performed before and 6–12 months after treatment in 21 children with ASD, 25 with PDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
1
3
1
Order By: Relevance
“…Our study reports no difference in NT-pro-BNP levels between repaired CoA patients and controls. This is in accordance with a recently published study by Eerola et al in which NT-pro-BNP levels in CoA patients, although higher than controls before and 6 months after repair, were similar at one year follow up [35]. This may be explained by the fact that left ventricular pressure overload is not expected to be significant in these patients since they do not present with serious hypertension, their NYHA class was not affected and LV dimension and function were within normal range.…”
Section: Neurohormonal and Immune Activation Late After Coa Repairsupporting
confidence: 93%
“…Our study reports no difference in NT-pro-BNP levels between repaired CoA patients and controls. This is in accordance with a recently published study by Eerola et al in which NT-pro-BNP levels in CoA patients, although higher than controls before and 6 months after repair, were similar at one year follow up [35]. This may be explained by the fact that left ventricular pressure overload is not expected to be significant in these patients since they do not present with serious hypertension, their NYHA class was not affected and LV dimension and function were within normal range.…”
Section: Neurohormonal and Immune Activation Late After Coa Repairsupporting
confidence: 93%
“…11 Eerola et al performed another study to investigate the association between peptide hormone levels and echocardiographic results, at 6 months and 12 months observation in ASD and coarctation of the aorta patients. 26 They reported decreased left ventricle diameters at six months after closure by about 20%, but in our study, left ventricular diameters decreased about 25% at three months after closure.…”
Section: Discussioncontrasting
confidence: 75%
“…9 In addition, a study showed higher BNP levels in their ASD group (79 pg/mL) compared to a control group (57 pg/mL) (P<0.05). 10 This shows that BNP levels can match echocardiography in diagnosing the size of ASD.…”
Section: Discussionmentioning
confidence: 85%